A bibliometric review of Islamic economics and finance bibliometric papers: an overview of the future of Islamic economics and finance - Mi'raj, Denizar Abdurrahman; Ulev, Salih (Qualitative research in financial markets, 2024)
Purpose Given the overlapping themes and periods in specific subjects within Islamic economics and finance bibliometric research, which may yield similar findings in bibliometric studies, it is essential to document the growth of Islamic economic and financial research using bibliometric methodologies. This study aims to understand better the critical bibliometric review trends and scientific advancements in Islamic economics and finance. Design/methodology/approach This study uses bibliometric analysis, collecting 46 Islamic economics bibliometric papers from the Web of Science Core Collection from 1975 to 2022. The authors generated top scientific scholars, keyword analysis, citation analysis, content analysis and conclusions for journal development using R Biblioshiny, VOSviewer, ATLAS.ti and Excel. Findings This study has established a comprehensive bibliometric framework for Islamic economics and finance bibliometric papers, encompassing all critical areas within the discipline and identifying any remaining research gaps. The major significant areas revealed were Islamic social finance and microfinance concerns, which are closely pertinent to the issues of ethics, corporate social responsibility and sustainability, respectively. The authors also identified opportunities for future bibliometric analyses in Islamic economics and finance, which include using more comprehensive databases, refining or broadening search strategies, using advanced techniques and units of analysis and suggesting themes for further exploration. Research limitations/implications The study relies merely on the Web of Science Core Collection database, which provides the most in-depth citations by source for the world’s scientific and scholarly research. Future research may consider expanding its scope to include other databases for a broader range of sources. Furthermore, due to the rise of bibliometric studies in Islamic economics and finance, this study also comments on the saturation of bibliometric studies conducted in several similar areas. While researchers bring their unique analytical perspectives to bibliometrics, this study provides a comprehensive view of existing research in Islamic economics and finance, highlighting well-explored topics and those that remain less studied. Thus, this could assist researchers in determining their future research priorities. Practical implications Policymakers in Islamic financial and economic institutions, including banking institutions, social, financial institutions and halal institutions, should be impacted by this research when making policies or conducting research. The viability of the current Islamic economic and financial ecosystem will be indirectly maintained and managed by these implications. Social implications This comprehensive meta-analysis in Islamic economics and finance is expected to impact the development and sustainability of the Islamic economic and financial ecosystem, promoting societal welfare through applying Islamic economics and finance. Originality/value This pioneering bibliometric analysis of Islamic economics and finance papers aims to offer insights and projections for future research in the field. This research contributes to the literature by examining various aspects, including evaluating literature on trending topics, analyzing papers related to research areas and conducting content analysis of existing bibliometric studies in Islamic economics and finance. It specifically groups these studies around fundamental topics, summarizes findings from contemporary research and identifies emerging research gaps.